2008
DOI: 10.1196/annals.1419.016
|View full text |Cite
|
Sign up to set email alerts
|

Old Acetogens, New Light

Abstract: Acetogens utilize the acetyl-CoA Wood-Ljungdahl pathway as a terminal electron-accepting, energy-conserving, CO(2)-fixing process. The decades of research to resolve the enzymology of this pathway (1) preceded studies demonstrating that acetogens not only harbor a novel CO(2)-fixing pathway, but are also ecologically important, and (2) overshadowed the novel microbiological discoveries of acetogens and acetogenesis. The first acetogen to be isolated, Clostridium aceticum, was reported by Klaas Tammo Wieringa i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
412
0
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 519 publications
(429 citation statements)
references
References 264 publications
1
412
0
6
Order By: Relevance
“…C. mayombei can also convert succinate to propionate and CO 2 (Kane et al, 1991). The capacity of acetogens to utilize a variety of electron donors and electron acceptors (Drake et al, 2008) reinforce the likelihood that acetogens could be metabolically active in the complex milieu of the gut contents of E. eugeniae.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…C. mayombei can also convert succinate to propionate and CO 2 (Kane et al, 1991). The capacity of acetogens to utilize a variety of electron donors and electron acceptors (Drake et al, 2008) reinforce the likelihood that acetogens could be metabolically active in the complex milieu of the gut contents of E. eugeniae.…”
Section: Discussionmentioning
confidence: 98%
“…However, which source of reductant (H 2 or formate) was used for methanogenesis remains unclear. Four molecules of H 2 or four molecules of formate are needed to produce one molecule of CH 4 (Hedderich and Whitman, 2006 Four molecules of formate are required to synthesize one molecule of acetate via acetogenesis (Drake et al, 2008). Thus approximately 9 mmol acetate per gram FW could have been formed from the approximate 34 mmol formate per gram FW transiently formed from glucose in [ 13 C]-glucose treatments.…”
Section: Discussionmentioning
confidence: 99%
“…1B). Acetogenic bacteria, including Holophaga foetida, Moorella thermoacetica, Oxobacter pfennigii, Thermoanaerobacter kivui (Muller, 2003;Drake et al, 2008;Fenchel, 2011;Müller and Frerichs, 2013), are possible substrate producers to acetoclastic methanogens. In this study, acetogenic bacteria were identified only in PIG sample (Fig.…”
Section: Microbial Community Analysismentioning
confidence: 99%
“…This microorganism was used to determine the acetyl-CoA pathway enzymology in the laboratories of Harland Goff Wood and Lars Gerhard Ljungdahl (Drake et al, 2008). To date, there are more than 100 acetogenic species isolated from a variety of habitats such as sediments, soils, sludge, and intestinal tracts of animals (Drake et al, 2008). Most of the microorganisms currently known to ferment syngas to ethanol are predominantly mesophilic with operating temperatures in the range of 30-40 °C (Munasinghe and Khanal, 2010a).…”
Section: Biocatalystsmentioning
confidence: 99%
“…This microorganism was used to determine the acetyl-CoA pathway enzymology in the laboratories of Harland Goff Wood and Lars Gerhard Ljungdahl (Drake et al, 2008). To date, there are more than 100 acetogenic species isolated from a variety of habitats such as sediments, soils, sludge, and intestinal tracts of animals (Drake et al, 2008).…”
Section: Biocatalystsmentioning
confidence: 99%